Ethanol Extract of Tithonia diversifolia (Hemsley) A Gray Standardized Ameliorates Hyperglycemia, Polyphagia, and Weight Loss in Diabetic Rats - Yulia Fauziyah; Sunarti Sunarti; Ita Fauzia Hanoum; Mae Sri Hartati Wahyuningsih (Molekul, 2018)
Diabetes mellitus is a state of chronic hyperglycemia which causes various complications. Traditionally, The Tithonia diversifolia (Hemsley) A Gray leaf has long been used for the treatment of diabetes. The aim of this study is to investigate the effect of the T. diversifolia leaf on blood glucose, polyphagia, and weight loss in a diabetic rat model. Rats were made diabetic with intraperitonial injection of Nicotinamide and Streptozotocin and divided into 5 groups. Group 1 were healthy rats, group 2 were diabetic rats, while groups 3, 4, and 5 were diabetic rats treated with 25, 50, and 100 mg/kg body weight of 70% ethanol extract of Tithonia diversifolia leaf respectively for 28 days. Blood was taken after treatment for measuring glucose. The ethanol extract of T. diversifolia leaf decreased blood glucose in diabetic rats (P<0.05). The ethanol extract of T. diversifolia leaf significantly suppresses polyphagia and improves diabetic rat weight (P <0.05). In conclusion, Tithonia diversifolia ethanolic extract has anti-hyperglycemic effect and ameliorated the effect of diabetes mellitus symptoms, namely polyphagia and weight loss.